SOME REFLECTIONS ON EDUCATION OF THE IDEAL GENERATION - Ruzmatov Abduvokhid Abdukakhkharovich (Journals Park Publishing, 2022)
Education and training are important factors in raising a perfect person. Taking this into account, the authors, relying on the opinions of eastern thinkers, put a special emphasis on the cooperation between the educational institution and the family in the article. Some of the reasons that hinder the education of a perfect person and their views on how to solve them were presented.
Keywords: perfect person, moral education, traditions, morality, correctness